Pengaruh Motivasi Kerja Dan Kepemimpinan Terhadap Produktivitas Kerja Karyawan Pada PT. Mahato Inti Sawit (MIS) Rokan Hulu - Dewi, Diana Sri (Eko dan Bisnis: Riau Economic and Business Review, 2023)
This research was conducted to determine the effect of work motivation and leadership on the work productivity of employees at PT. Mahato Inti Sawit (MIS) Rokan Hulu. The population in this study were all employees at PT. Mahato Inti Sawit (MIS) Rokan Hulu until December 2020 totaled 145 people. The sample taken was 59 people referring to the Slovin formula, the data collection techniques in this study were questionnaires and observations. Data analysis in this study used descriptive and quantitative methods. Descriptive is comparing the actual reality with theories that have to do with the problem in order to draw a conclusion and tabulated it in the form of frequency distribution tables. While the quantitative method is research based on data that can be calculated to produce a solid estimate. The results of multiple linear regression in this study are Y = 39,638+0,360+0,141+e. Motivation (X1) where the t-count value of 4.615 is greater than the t-table of 1.67256 with a significance value of 0.000 and leadership (X2) where the t-count value of -1.438 is smaller than the t- table value of 1.67252 with a significance value of 0.156. The calculated F value of 13.475 is greater than the F table value of 3.162 with a significance value of 0.000. The value of R square in the table above means that the variation of work motivation and leadership variables can explain the company's productivity variable by 57.0%.